Dysbiosis of the microbiome in gastric carcinogenesis - Castaño-Rodríguez, N.; Goh, K.L.; Fock, K.M.; Mitchell, H.M.; Kaakoush, N.O. (Nature Publishing Group, 2017)
The gastric microbiome has been proposed as an etiological factor in gastric carcinogenesis. We compared the gastric microbiota in subjects presenting with gastric cancer (GC, n = 12) and controls (functional dyspepsia (FD), n = 20) from a high GC risk population in Singapore and Malaysia. cDNA from 16S rRNA transcripts were amplified (515F-806R) and sequenced using Illumina MiSeq 2 × 250 bp chemistry. Increased richness and phylogenetic diversity but not Shannon's diversity was found in GC as compared to controls. nMDS clustered GC and FD subjects separately, with PERMANOVA confirming a significant difference between the groups. H. pylori serological status had a significant impact on gastric microbiome α-diversity and composition. Several bacterial taxa were enriched in GC, including Lactococcus, Veilonella, and Fusobacteriaceae (Fusobacterium and Leptotrichia). Prediction of bacterial metabolic contribution indicated that serological status had a significant impact on metabolic function, while carbohydrate digestion and pathways were enriched in GC. Our findings highlight three mechanisms of interest in GC, including enrichment of pro-inflammatory oral bacterial species, increased abundance of lactic acid producing bacteria, and enrichment of short chain fatty acid production pathways.